2012
DOI: 10.2147/ijwh.s24948
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted laparoscopy for the detection and diagnosis of endometriosis: safety, reliability, and invasiveness

Abstract: Endometriosis is a highly enigmatic disease with multiple presentations ranging from infertility to severe pain, often causing significant morbidity. Video-assisted laparoscopy (VALS) has now replaced laparotomy as the gold standard for the diagnosis and management of endometriosis. While imaging has a role in the evaluation of some patients, histologic examination is needed for a definitive diagnosis. Laboratory evaluation currently has a minor role in the diagnosis of endometriosis, although studies are unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…2,19 These techniques involve precise and directed excision and ablation of all endometriotic implants and restoration of normal anatomy. Bowel and bladder surgery in the treatment of endometriosis is completed as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,19 These techniques involve precise and directed excision and ablation of all endometriotic implants and restoration of normal anatomy. Bowel and bladder surgery in the treatment of endometriosis is completed as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…The treatment of endometriosis is carried out per previously described protocols for fertility-sparing treatment of endometriosis. 2 , 19 These techniques involve precise and directed excision and ablation of all endometriotic implants and restoration of normal anatomy. Bowel and bladder surgery in the treatment of endometriosis is completed as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Laparoscopy is the recommended surgical technique for the treatment of endometriosis, regardless of its stage [ 122 ]. The best therapeutic effects are achieved as a result of the combination of surgical treatment with pharmacological treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…This, associated with the fact that laparoscopy is far from 100% accurate (Khan et al, 2014;Walter et al, 2001;Wykes et al, 2004), raises the question of whether laparoscopy should be indicated in all suspected cases of endometriosis. Laparoscopy obviously has its merit in both diagnosis and treatment of endometriosis (Schipper & Nezhat, 2012); however, it could be argued that better screening of patients to be submitted to laparoscopy, not only for the presence of specific symptoms and by physical examination but also for the presence of serum biomarkers, may benefit patients.…”
Section: Discussionmentioning
confidence: 99%